Context-Based Learning in Turkish Idioms Learning by International University Students - Sanal, Seda Ozer (My University, 2023)
This research examines international university students' experiences learning Turkish idioms in context-based learning (CBL) digital environment. Twelve international students studying at Fırat University and nine students whose native language does Turkish voluntarily participate in the study. In this study, in which quantitative and qualitative data were collected, the embedded mixed method research design was used to examine how individual and collaborative efforts of international students in context-based learning-based environments support their learning of Turkish idioms. Four sources were identified for the data of the study: (1) log data, (2) focus group interview data, (3) Turkish idiom achievement test, and (4) follow-up interview. Analysis of its data proved that the context-based e-learning environment constitutes an effective language-learning process. The study presents a very effective presentation of a context-based learning environment in the digital environment and the change in student behaviors and performances. This study, which shows the social constructivist approach in general and the effectiveness of CBL in particular, advocates the importance of peer support and collaboration.
Keywords: Language teaching; peer support; context-based learning; mixed method research design